Unraveling the effects of leader perfectionism on team dynamics: an emotion-motivation perspective - Yamei Liu; Zhaopeng Liu; Danting Chang; Chi Zhang (Humanities & Social Sciences Communications)
Abstract Perfectionism has gained increasing attention from researchers due to its significant impact on work and non-work outcomes. However, it remains unclear whether the influence of perfectionism on teams is positive or negative. Our research provides clarity on the group effects of leader other-oriented perfectionism. Drawing from the literature on perfectionism and approach-avoidance emotivation theory, we investigate the influence processes (e.g., team affective tones and team performance motivations) and boundary conditions (e.g., team trait resilience) of leader perfectionism on team prosocial behavior and team cheating behavior. Data collected from 152 leaders and 699 employees reveals that leader other-oriented perfectionism positively influences team energy tone, which subsequently enhances team performance approach motivation and facilitates team prosocial behavior. Additionally, leader other-oriented perfectionism positively impacts team anxious tone, which subsequently promotes team performance avoidance motivation and facilitates team cheating behavior. Moreover, team trait resilience strengthens the former chain of processes while weakening the latter. These results shed light on the complex dynamics between leader other-oriented perfectionism, team affective tone, motivation, and ethical behaviors, highlighting the significance of team trait resilience as a boundary condition in these relationships. Theoretical and practical implications are provided.